Narratives of Charles Darwin Down Under. (August 2021) - Hesketh, Ian
Abstract: Despite the fact that Charles Darwin spent several months in Australia in the final year of his Beagle voyage that circumnavigated the globe, most studies that deal with Darwin's life or his discovery of evolution spend little time discussing his Australian period, if it is mentioned at all. His time there is largely deemed to have produced little of significance in comparison to his visits to other places such as the Galápagos Islands, which has long been mythologized as providing the key sources of observable data that ultimately led Darwin to develop his evolutionary speculations. In recent years, however, Darwin's period in Australia has received more attention, most notably a series of studies detailing the observations and connections Darwin made while in New South Wales, Tasmania, and King George Sound. While much of this literature has provided an important corrective to previous Darwin scholarship that had largely ignored Darwin's period in Australia, it has also worked to perpetuate a romantic and heroic view of scientific discovery by suggesting that Darwin's key "evolutionary revelation" was made not in the Galápagos Islands but in the Blue Mountains, a claim that has been recently made in print and online. This paper therefore examines the historical literature on Darwin Down Under, focussing in particular on this recent romantic turn that seeks to situate Australia as the key site of inspiration for Darwin's theory of evolution.